#TITLE_ALTERNATIVE# - SULISTYANTO (NIM 22295006), DJOKO
Two-phase multi rate test analysis could be done with some modifications of single-phase and application of pseudopressure function. This study is to examine the application the pseudopressure function concept into two-phase flow, oil and gas. Pseudopressure concept basically combine parameters of rock and fluid properties (formation volume factor and viscosity) to be a pseudo parameter. Hence the diffusivity equation become similar to the single phase diffusivity equation. The objective of this research study is to apply the pseudopressure function into two-phase multi rate test analysis with normal flow rate and reverse flow rate schedules. The study was concluded using one dimension and radial cylindric of three-phase reservoir mode. This mode was applied to simulate well test for multi rate under simultaneously producing fwo-phase, oil dan gas using hypotetic data. The mode is run with sequence of normal and reverse flow rate under the same production time. Validation with the simulation input data yields very good results. Especially, the reverse sequence flow rate gives better results than the normal sequence.